Fifth IEEE International Conference on Data Mining (ICDM'05)
DOI: 10.1109/icdm.2005.45
|View full text |Cite
|
Sign up to set email alerts
|

Combining Multiple Clusterings by Soft Correspondence

Abstract: Combining multiple clusterings arises in various impor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…Hard community matching can be performed by selecting the best matching pair of communities one by one, avoiding conflict with already selected pairs [10,11] or using greedy algorithms like CLUMPP [20]. Soft community matching can be done so as to minimize the distance between the two matrices [27]. In computer vision, community matching has been Table 1: Table of Notations done by using cluster features like position, intensity, shape and average gray-scale difference [23], and degree of match between surrounding clusters [28].…”
Section: Related Workmentioning
confidence: 99%
“…Hard community matching can be performed by selecting the best matching pair of communities one by one, avoiding conflict with already selected pairs [10,11] or using greedy algorithms like CLUMPP [20]. Soft community matching can be done so as to minimize the distance between the two matrices [27]. In computer vision, community matching has been Table 1: Table of Notations done by using cluster features like position, intensity, shape and average gray-scale difference [23], and degree of match between surrounding clusters [28].…”
Section: Related Workmentioning
confidence: 99%
“…Many cluster ensemble approaches use a co-association matrix to accumulate the similarity between data points by all given clusterings [14,36]. Other approaches focus on finding the correspondence between cluster labels produced by different clustering systems [26]. In many cases, the numbers of clusters in the final clustering is preset.…”
Section: Clustering Ensemblesmentioning
confidence: 99%
“…The problem of combining multiple clusterings into a single consolidated clustering has been studied extensively under the names of clustering ensembles [36], clustering combination [14,26] or clustering aggregation [16] in recent years. The final clustering is usually the one that agrees the most with the given clusterings.…”
Section: Clustering Ensemblesmentioning
confidence: 99%
“…Creating multiple partitions of a given data set has been examined in several ways [1,2,5,6,7,8,12,14]. In [1] hyperedges are formed from each clustering solution represented as a label vector.…”
Section: Related Workmentioning
confidence: 99%
“…There has been research on combining ensembles of clustering solutions [1,2,5,6,7,8,12,14] where each clustering solution is represented by a label vector whose Prodip length is equal to the number of examples from which the solution was obtained. It has been shown that combining this ensemble of clustering solutions produces a good final global partition.…”
Section: Introductionmentioning
confidence: 99%